Dampak Motivasi Guru Terhadap Prestasi Belajar Siswa di SD NU Galur - M. Zulfa Chusni Mubarok; Sutiyono (Journal of Primary Education Research, 2024)
This study aims to analyse the impact of teacher motivation on student learning achievement at SD NU Galur based on Maslow's needs theory including physiological needs (eating, drinking, resting, learning comfort), security (emotional support, guidance and counselling), attention and affection (personal and interpersonal support), appreciation (verbal and nonverbal appreciation), and self-actualisation (providing learning challenges according to student abilities). This study aims to analyze how the fulfilment of student needs has an impact on improving student learning achievement seen from the difference in pretest and posttest results. The study used a One Group Pretest-Posttest experimental quantitative research design, where all students took an initial test (Pretest) before receiving teacher motivation treatment in the form of fulfilling students' basic needs based on Maslow's theory and a final test (Posttest) after being given treatment. The research subjects were 26 grade 2 students of SD NU Galur. Data collection techniques used learning achievement tests (Pretest-Posttest), observation sheets to observe the provision of teacher motivation treatment and documentation. The test instrument was tested for validity using content validity and reliability test with Cronbach alpha coefficient of 0.85 (high). Data analysis included Shapiro-Wilk normality test and Wilcoxon Signed-Rank hypothesis test to see the difference in Pretest and Posttest results. The results of the analysis of the pretest average score of 71.54 with a standard deviation of 17.594 increased to 93.08 with a standard deviation of 9.703 on the posttest indicating that there was a significant increase in student learning achievement after teachers fulfilled students' basic needs. The Shapiro-wilk normality test showed that the pretest and posttest data were not normally distributed (pretest Sig. 0.001; posttest Sig. 0.000). Furthermore, non-parametric hypothesis testing with the Wilcoson Signed-rank formula results in a Z value of -4.510 and Asymp. Sig. (2-tailed) = 0.000<0.05 meaning that there is a significant difference between pretest and posttest scores. Researchers suggest that teachers continue to improve their skills in providing motivation, then the school is advised to provide training to teachers related to fulfilling student needs, and for further research it is recommended to use a control group for more valid and strong research results.